ChemInform Abstract: Highly Selective Phosphinylphosphination of Alkenes with Tetraphenyldiphosphine Monoxide. Issue 50 (November 2016) - Sato, Yuki; Kawaguchi, Shin‐ichi; Nomoto, Akihiro; Ogawa, Akiya
Abstract: Contrary to tetraphenyldiphosphine, which does not add to C—C double bonds efficiently, tetraphenyldiphosphine monoxide (II) can engage in a radical addition to various alkenes and even alkynes.